Redução de danos e o cuidado de si: sobre quais cuidados falamos? - Silva, Rubens Espejo da (2020)
Is there a possibility that men who are in a shelter centrein the city of São Paulo, who use alcohol and other drugs take care of themselves? In this context, is harm reduction conducive to self-care practices? These are the two major axes that run through this research. Research this writing as a metaphor for a nautical voyage. Men are housed in the shelter in the most diverse situations. Many of them have a history of “abusive” use of alcohol and other drugs, family and / or job losses, and who have already been hospitalized and / or imprisoned. Therefore, the general objective of this paper was to understand what forms of self-care are practiced by users of alcohol and other psychoactive substances, in other words, how they take care of themselves. Self-care is a concept and we seek in Foucault, as well as in the field of nursing, considerations on the subject. In order to reach the objective, conversation rounds were held with the host from August to December 2018. The themes were: health care; stigma and prejudice against drug users; mental health; harm reduction, etc. We use the logbook/field diary as a record of the events that the wheels and the experience inside and outside the welcome center caused. We also held an individual interview conversation to delve into what was talked about in the wheels. This is a qualitative research based on social constructionism as an epistemological basis, and as a theoretical-methodological framework the analysis of discursive practices. Through logbook/field diary analysis, we present several issues that have emerged, but mainly how alcohol and other drug users take care of themselves. In this paper we bet on the production of autonomy of people who use drugs, and also warn that the problem is not only in drugs, quite the opposite. Finally, we propose a reflection on how prejudice, morality and the prohibitionist mentality end up giving centrality to the drug, and, consequently, to the nonobservation of the person, because the “drug” has as its primary function to obliterate various vulnerabilities and violations of human rights that these men have suffered and still suffer